The Effect of Teaching Style and Eye-Hand Coordination on Learning Outcomes in Tennis Field Groundstrokes - Afri Tantri; Benny Aprial. M; Mashud Mashud (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to find differences about the effect of reciprocal teaching style, practice style and the inclusion style, as well as the level of eye, hand and foot coordination of students on student learning outcomes of groundstrokes. The sample is students who are divided into groups who receive an exercise and reciprocal teaching style by considering the ability of eye, hand and foot coordination. This research uses 2x3 Factorial Design. The research population was 118 students, the research sample was taken based on Verduci's theory 27%, the category of high eye-hand-foot coordination group was students who included in the 27% highest score, the category of low eye-hand-foot coordination group was students who included in the lowest 27% score. Testing of eye, hand and foot coordination was carried out with a test of eye, hand and foot coordination. While the groundstroke ability is done by testing groundstrokes forehand and backhand. Based on the results of the test analysis, it was found that the overall teaching style of the group with high eye, hand and foot coordination had better results. There is an interaction between teaching style and eye, hand and foot coordination on the learning outcomes of groundstrokes.